What's Changed? A Comparison of Army Suicide Surveillance Data to Cases from 1975 to 1982. Issue 1 (28th December 2016) - Reger, Mark A.; Reger, Greg M.; Krieg, Christina; Pruitt, Larry; Smolenski, Derek J.; Skopp, Nancy A.; Bush, Nigel
Abstract : US Army suicide rates increased significantly in the last decade and have remained high. To inform future research hypotheses, Army suicide surveillance data (2012–2014) were compared to similar Army data for suicides from 1975 to 1982. Preliminary data suggest that suicide rates increased across most demographic groups, but may have decreased among divorced soldiers. Mental health utilization increased over time. Legal problems and physical health problems were identified in a higher percentage of cases in the recent data relative to the 1975–1982 era. Potential implications for suicide prevention are discussed.